2020
DOI: 10.20944/preprints202004.0397.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Forecasting COVID-19-Associated Hospitalizations under Different Levels of Social Distancing in Lombardy and Emilia-Romagna, Northern Italy: Results from an Extended SEIR Compartmental Model

Abstract: The outbreak of coronavirus disease 2019 was identified in Wuhan, China, in December 2019. As of April 17, 2020, more than 2 million cases of COVID-19 have been reported worldwide. Northern Italy is one of the world's centers of active coronavirus cases. In this study, we predicted the spread of COVID-19 and its burden on hospital care under different conditions of social distancing in Lombardy and Emilia-Romagna, the two regions of Italy most affected by the epidemic. To do this, we used a Susceptible-Expose… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…Continuous time Markov chain models are regularly used to model transmission of diseases. To date most of the work done to model COVID-19 has used deterministic modelling which gives an approximation of the mean of the stochastic epidemic curves [12,[21][22][23]. However, the deterministic curves will miss the likely timing of the peak of incidence since averaging over values does not imply averaging over time.…”
Section: Discussionmentioning
confidence: 99%
“…Continuous time Markov chain models are regularly used to model transmission of diseases. To date most of the work done to model COVID-19 has used deterministic modelling which gives an approximation of the mean of the stochastic epidemic curves [12,[21][22][23]. However, the deterministic curves will miss the likely timing of the peak of incidence since averaging over values does not imply averaging over time.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, further works have been trying to predict the behavior of some COVID-19 related variables through the use of exponential models as well as dynamic SIR-based models ( Chen et al., 2020 ; Fanelli and Piazza, 2020 ; Remuzzi and Remuzzi, 2020 ; Reno et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…We simulate COVID-19 spread with rapid testing and model disease outcomes in three regions in the United States and São José do Rio Preto, Brazil -the site of the clinical validation study -using publicly available data. To date, COVID-19 modeling describes the course of disease spread in response to social distancing and quarantine measures, and a previous simulation study has shown that frequent testing with accuracies less than qRT-PCR, coupled with quarantine process and social distancing, are predicted to significantly decrease infections 12,17,[23][24][25][26][27] . This is the first modeling system using publicly-available data to simulate how potential public health strategies based on testing performance, frequency, and geography impact the course of COVID-19 spread and outcomes.…”
Section: Introductionmentioning
confidence: 99%